Industries and agricultural background influences on career decision self-efficacy - Winingsih, Evi; Setiawati, Denok; Pratiwi, Titin Indah (KONSELOR, 2023)
Career is an important aspect of human life and its stability is determined by Career Decision-making Self Efficacy (CDSE). This study aims to compare high school students' CDSE between those living in industrial and agrarian areas. Subjects in this study were 309 high school students and 309 vocational students from both areas. Data were collected using the CDSE-SF instrument developed by Nancy E. Betz. Mann Whitney comparative test was used to analyze the data in this study. The results show that there were differences in the CDSE significance level of students from both areas. Accordingly, the results find that three of the five aspects of senior high school students' CDSE show their The results of data analysis showed significant differences in the five aspects of student CDSE in industrial and agricultural areas.The different value between both students occurs due to the difference in goal and career directions which is highly possible because of several factors that were not discussed in this study.